2000
DOI: 10.2114/jpa.19.225
|View full text |Cite
|
Sign up to set email alerts
|

Low-Energy Diet in Atopic Dermatitis Patients. Clinical Findings and DNA Damage.

Abstract: Undernutrition without malnutrition (lowenergy diet) increases maximum longevity, reduces the incidence of several cancers and delays their onset, in animal studies. It has also been demonstrated by experimental study that caloric restriction provides a beneficial effect on various inflammatory diseases. In this study, we offered a low-energy diet to patients with atopic dermatitis (AD). Nineteen adult patients (5 males and 14 females aged 15 to 36 years) were enrolled in the study which lasted 8 weeks. The en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 16 publications
1
28
0
Order By: Relevance
“…Previously we reported that this therapy caused a reduction in oxidative DNA damage measured by urinary secretion of 8-OHdG (Kouda et al, 2000). In this study to assess the mechanisms in more detail through which this therapy affected AD, several immunological markers were examined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously we reported that this therapy caused a reduction in oxidative DNA damage measured by urinary secretion of 8-OHdG (Kouda et al, 2000). In this study to assess the mechanisms in more detail through which this therapy affected AD, several immunological markers were examined.…”
Section: Discussionmentioning
confidence: 99%
“…This therapy mainly consists of a lowenergy and vegetarian diet (Kouda, 1995). Previously we reported that a low-energy diet reduced inflammatory symptoms of patients with AD (Kouda et al, 2000). The a i m o f t h e p r e s e n t s t u d y w a s t o i d e n t i f y t h e immunological mechanisms of the treatment for AD.…”
Section: Introductionmentioning
confidence: 94%
“…Concerning inflammatory disease, a relationship between asthma and obesity has been suggested in several epidemiological studies (Story, 2007). In a clinical study, a low-energy diet reduced inflammatory symptoms and oxidative damage in patients with atopic dermatitis (Kouda et al, 2000). A case of a patient with atopic dermatitis and repeated one day fasting has also been reported (Nakamura et al, 2003).…”
mentioning
confidence: 99%
“…A pilot study showed that restriction of energy intake to 55% of nutritional requirements for 8 weeks significantly alleviated the symptoms of atopic dermatitis. 26) Moreover, alternate-day restriction of food intake regimen (repetition of consumption of 320-380 calories one day and ad libitum intake the other) for 8 weeks improved quality of life in subjects with body-mass-index >30 and moderate asthma. 27) These results encourage us to clarify the beneficial effects of restriction of food intake and to apply them to remedy dysregulated immune functions and to maintain health.…”
Section: Discussionmentioning
confidence: 98%